18F-Fluciclovine–Avid Pulmonary Hamartoma. (November 2021) - Baldeosingh, Sacha C.; Rowe, Steven P.; Greco, Stephen C.; Paller, Channing J.; Goel, Reema
Abstract : Abstract: A 73-year-old man with history of grade group 1/Gleason 3 + 3 = 6 prostate adenocarcinoma status post prostatectomy had subsequent biochemical recurrence with serum prostate-specific antigen level of 2.4 ng/mL. He underwent an 18 F-fluciclovine PET/CT scan that demonstrated a left prostate bed recurrence and an incidental 18 F-fluciclovine–avid smooth-edged solitary lung nodule with internal fat attenuation. Such uptake of 18 F-fluciclovine in a lung hamartoma could be mistaken for prostate cancer metastasis. Given the increasing use of advanced imaging for prostate cancer, there is need for the imaging specialist to know about pitfalls and how to interpret them.